Implementasi Agile Software Development dalam Perancangan Sistem Pengelolaan Limbah Sampah - Imam Saputra; Pristi Sukmasetya; Ardhin Primadewi (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
Waste is the residual material from human activities that has no utility; as a result, it can have various negative impacts. However, the issue of waste can be addressed through one method, which is a waste bank. One example of the implementation of a waste bank is in the Karang Hamlet. The waste bank management process at the Cempaka Waste Bank in the Karang Hamlet is still done manually by recording all processes and data in books. This is highly susceptible to errors or mistakes when recording data and requires a significant amount of time for data input and retrieval. To address these issues, the researcher aims to develop a waste management system based on a website to assist and streamline waste bank operations at the Cempaka Waste Bank in the Karang Hamlet. The data collection methods used include observation, interviews, and a literature review, and the software development method utilizes the Agile Software Development method because it is a lightweight and suitable approach for this research. Before testing with potential users, the system is initially tested using black-box testing, and the results show that the system functions properly, and its features work as intended